COMMON CULTURAL HERITAGE OF THE TURKISH WORLD: NAURUZ - Emrah ÇETİN (Fırat University, 2019)
Culture is a common way of life of a nation. The most important elements of culture are traditions, customs and beliefs. The reflections of these nations’ traditions, customs and beliefs to the social life are “festivals”. All nations have special days for comemorating important events experienced in the history, keeping alive the customs, the traditions and fulfilling the religious beliefs. And Nauruz is one of these special days kept alive throughout the history of the Turkish world. It is the national holiday of the Turkish world. If Nauruz traditions of the Turks are taken into consideration through Central Asia-Seljuk-Ottoman-Republic process, it shows continuity. Today, Nauruz festival continues to be celebrated with the same enthusiasm in Turkey, Iran, Afghanistan, Pakistan, Turkmenistan, Tajikistan, Kyrgyzstan, Azerbaijan and Kazakhstan located within the historical boundaries of the Seljuk Empire. In this aspect, this tradition that has been living for thousands of years in the Turkish world is the common cultural heritage of the Turks. Turkish people’s loyalty to their families, traditions, customs and states brought Nauruz to these days..